Iron Fortification and Inulin Supplementation in Early Infancy: Evaluating the Impact on Gut Microbiome in a Piglet Model - Jungjae Park; Cynthia Jinno; Saumya Wickramasinghe; David A Mills; Yanhong Liu; Bo L Lönnerdal; Peng Ji (Current Developments in Nutrition)
Background: Prophylactic iron fortification in infant formula effectively prevents iron deficiency anemia. However, the low absorption rate results in excess unabsorbed iron accumulates in colon, where it has been linked to harmful microbiota changes and increased diarrheal incidence. Prebiotic oligosaccharides have shown promise in mitigating these adverse effects, but the role of inulin or synbiotic supplementation with inulin-fermenting lactic acid bacteria in modulating early gut microbiome under iron fortification remains understudied. Objectives: This study used a neonatal pig model to investigate the effects of iron fortification and inulin supplementation, with or without Ligilactobacillus agilis YZ050 (L. agilis), on gut microbiome. Methods: Twenty-four piglets were stratified and randomly assigned into 1 of the 4 dietary treatments from postnatal day (PD) 2: iron-adequate milk (AI), high-iron milk (HI), high-iron milk with 5% inulin (HIP), or HIP milk with oral gavage of L. agilis every third day (HIS). Piglets were individually housed and fed milk in proportion to body weight in 14 meals daily, simulating formula feeding in infants. Fecal and colonic microbiome were analyzed via 16S rRNA sequencing, with microbial diversity and relative abundance analyzed using QIIME2 and R. Results: Iron fortification, regardless of inulin supplementation, decreased α-diversity compared with AI. β-Diversity showed clustering of HIP and HIS samples, which were distinct from AI and HI. Although iron fortification had minor impact on microbial composition, inulin supplementation significantly modified microbiome diversity, increasing Prevotella, Megasphaera, and Lachnospiraceae_NK3A20_group species, while reducing Bacteroides and Ruminococcus. Colonic microbiome shifted from Bacteroides-dominant enterotype in AI and HI groups to Prevotella-dominant enterotype in HIP and HIS groups, indicating enhanced fiber degrading capacity. Despite its inulin-fermenting property, L. agilis showed limited colonization and minimal microbiome impact. Conclusions: Inulin supplementation significantly influenced gut microbiome, shifting enterotype from Bacteroides to Prevotella. dominance and overriding the effect of high-iron fortification in a milk-fed piglet model.